Sustainable synthesis, in silico evaluation of potential toxicity and environmental fate, antioxidant and UV-filtering/photostability activity of phenolic-based thiobarbituric derivatives. Issue 1 (2nd January 2022) - Rioux, Benjamin; Mention, Matthieu M.; Alarcan, Jimmy; Abiola, Temitope T.; Peyrot, Cédric; Brunissen, Fanny; Braeuning, Albert; Stavros, Vasilios G.; Allais, Florent
ABSTRACT: The recent ban of some organic UV-filters – such as oxybenzone or octinoxate – considered toxic for coral reef, has heightened the need for eco-friendly alternatives, especially those synthesized using green approaches that reduce the carbon footprint. In this context, several thiobarbituric acid derivatives were synthetized from bio-based p -hydroxybenzaldehydes ( e.g. vanillin, syringaldehyde) through a high-yielding sustainable Knoevenagel condensation, and their UV-filtering activity, stability and antiradical properties were investigated. The results showed promising UVA and blue light coverage over time, as well as competitive EC50 values in comparison to commercial antioxidants ( i.e. BHA and BHT). In order to evaluate the potential of these molecules as substitutes to current petroleum-based UV-filters, the potential toxicity and fate in environment of these new compounds were evaluated in silico . This screening did not show a critical potential for toxicity, making them promising candidates for further in vitro and in vivo assessment. GRAPHICAL ABSTRACT: UF0001